Analysis of the Impact of Government Expenditure on Education, Health and Facilities and Economic Growth on Poverty in Indonesia: - - Ervinda Anggun Novitasari; Wiwin Priana Primadha; Wirya Wardaya (International Journal of Economics, Business and Innovation Research, 2024)
Poverty is one of the classic problems that is very big and fundamental because this problem has been a problem for a long time, and from time to time the Government needs to function in overcoming primary development problems related to poverty, one of which is through fiscal policy in the allocation of funds issued. This study analyzes the influence of government spending in the education, health, and infrastructure sectors, as well as economic growth on poverty rates in the poorest countries in the Western and Eastern regions of Indonesia. Using quantitative methods and secondary data from official sources, the analysis was carried out by panel data regression. The results of the study show that government spending in the education sector does not have a significant effect on poverty rates, while spending in the health and infrastructure sectors has a negative and significant influence, contributing to reducing poverty rates. In addition, economic growth did not show a significant influence on poverty levels, indicating that the benefits of such growth were uneven. This study recommends the need for more effective government policies in allocating budgets for sectors that can reduce poverty and promote inclusive growth.